Psychogenetic and psycho-physiological markers of cognitive abilities (The Journal of Psychology and Sociology, 2019)
This article is devoted to the actual problem of an integrative approach in the study of cognitive abilities using psychogenetic, psycho-physiological and psychometric methods. Modern studies of genetic markers of cognitive abilities are considered. The most significant achievements in the field of the recently appeared new direction of psychogenetics are noted. Scientific studies of the neurophysiological basis of abilities within the framework of cognitive neuroscience are also indicated. The results of modern studies of cognitive abilities, conducted using the methods of cognitive neuroscience, are considered. The results of recent psychogenetic studies of cognitive abilities, the limited predictive power of this research method, the complexity and systemic deficiencies of establishing genetic markers of cognitive abilities are reviewed. The conclusion about the promising use of the three-component “attention system” and the research of M. Pozner’s executive control is substantiated. The possibilities of electroencephalography (EEG) in combination with the tests of the Attention Network Task test to assess cognitive abilities were revealed.The necessity of combining the above methods to address the issues of early diagnosis of cognitive abilities is substantiated. The necessity of further detailed study of this problem on the basis of an integrative integrated approach is indicated. The idea of ​​combining psychogenetic studies, EEG methods in combination with the Attentional Network Task tests to assess executary control to establish markers of cognitive abilities is substantiated. According to the author, this approach will allow developing a system of science-based criteria for the effectiveness of human capital development programs.Keywords: markers of cognitive abilities, executive control, psychogenetics, electroencephalography